THE VILIBOR–EURIBOR SPREAD DYNAMICS DURING THE RECENT FINANCIAL CRISIS - Lapinskas, Vytenis (Ekonomika, 2011)
This article deals with the influence of the international financial crisis on the Lithuanian interbank market interest rates. Specifically, VILIBOR–EURIBOR spread dynamics over the period from the beginning of 2005 until the end of 2010 is analysed. The objective of the study was to estimate and describe the main factors affecting the VILIBOR spread. Methods used in the study include a systemic analysis of related studies, historical data analysis and statistical testing.Several episodes of increased market volatility could be clearly identified during the period, under study and the volatility of the data series as well as changes in their statistical properties and interdependence make the statistical analysis of the relationship very complicated. Statistically robust results could be achieved only after introducing several restrictions. The EURIBOR, RIGIBOR and Lithuanian CDS indexes have been found to explain more than 40 percent of the largest VILIBOR spread changes.